Comparison Pai-1 Level in Type 2 Diabetes Mellitus with and Without Diabetic Foot Ulcer - Sholat, Alfi Dewi; Gatot, Dairion; Handayani, Savina; Mardia, Andri Iskandar; Syafril, Santi (Sumatera Medical Journal, 2018)
In type 2 diabetes mellitus, there are changes in hemostasis components, including overexpression of PAI-1. By these facts, the authors are interested in conducting the study of PAI-1 level in diabetic patients with and without foot ulcer. Methods: The sample of this research was collected cross-sectionally on 20 type 2 diabetic patients with foot ulcer and 20 without foot ulcer. Blood samples were taken to measure serum PAI-1 level, complete blood count and hemostasis screening test. Results: Statistical analysis showed there are significant differences in hemoglobin, trombosit, Fibrinogen and D-dimer levels in the ulcer and non-ulcer groups but no significant difference in PAI-1 level. Conclusions: No higher PAI – 1 level were found in diabetic foot ulcer group than those without diabetic foot ulcer. There was no significant difference between PAI-1 level and grade of diabetic foot ulcer.